Verification method AT LAND CONDITIONS of linear RESOLUTION on azimuth in a radar with the aperture synthesis of space basing - S. R. Heister; N. M. Naumovich; G. N. Demidovich; V. T. Revin; S. P. Urbanovich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
By working out of a radar with the aperture synthesis of the aerial (RAS) of space basing there is a necessity of its debugging and verification at the land conditions. The most difficult verification task is requirement performance on resolution maintenance of RAS on an azimuth. It is caused by the given resolution provided in RAS at an orbit during stable moving in space with a speed about 7,6 km/s. The verification method of maintenance of the demanded linear resolution of RAS on an azimuth in land conditions with turned synthesis of aerial aperture is offered. It operates when RAS is unmoved and objects of resolution are placed at a moving ship.